Anthracnose - Monica L. Elliott; Philip F. Harmon (EDIS, 2011)
Identify and control for this disease that often appears as reddish-brown spots surrounded by a narrow yellow halo, primarily in centipedegrass. This revised 2-page fact sheet was written by M. L. Elliott and P. F. Harmon, and published by the UF Department of Plant Pathology, February 2011.